PASTI-CARE: Preschool Student Progress Tracking System - CHE ROZAIME, NUR AMYKA ADNIN; AMAN, HANNANI (Applied Information Technology And Computer Science, 2025)
The rapid evolution of education demands efficient systems for managing student progress. Current manual methods which are reliant on physical records, are prone to inefficiency, errors, and damage, creating challenges for teachers and delaying communication with parents in PASTI Al-Fateh 2. To address this, an object-oriented system developed using Python, called PASTI-CARE integrates modules for student registration, progress tracking, profiles, parent interaction, and data analytics. PASTI-CARE will be implemented to solve the problems for the selected class, 4 Adnin. The system enhance communication between teachers and parents, streamline progress tracking, reduce workloads, and encourage the holistic development of students. The requirements and designs of the system has been analysed using object oriented analysis and design method. Therefore, the UML diagrams have been generated.  The system creates a holistic learning environment by providing insights into academic, social, and Islamic skill development, ultimately supporting the growth and engagement of students. Functional and user acceptance testing confirmed the system’s reliability and ease of use. Future improvements include support for multiple class levels, syllabus customization, mobile application, and a gallery feature for event documentation.